Impact-Loss-Compensated Wideband Vibrational Energy Harvesting Using a Hybrid BaTiO_{3}/SU-8 Nanocomposite as the Active Layer - Nadeem Tariq Beigh; Sourav Naval; Dhiman Mallick (PRX Energy, 2022)
Mechanical impact-induced nonlinearity proves to be effective in the tunable broadening of the frequency response in vibrational energy harvesters at various size scales. However, the substantial impact-induced power loss in impact-driven energy harvesters (IDEHs) negates such advantages. Here, an in situ power compensation mechanism is introduced to recover the impact-induced losses, and thereby, substantially enhance the energy harvesting efficiency. The proposed scheme is realized by designing an IDEH, where a dual transduction barium titanate/SU-8 based nanocomposite is used as the active layer. The piezoelectric transduction of the nanocomposite is used for conventional wideband power generation from the IDEH, whereas the additional triboelectric property enables the impact-induced loss compensation. The proposed improvement is quantified using a suitably defined figure-of-merit “power integral” (PI) that integrates the total power generated over the entire operational frequency range. The PI shows a shift from the region of impact loss to the region of compensation at input accelerations of <1.5 g. Through suitable device engineering, the hybrid IDEH is experimentally shown to achieve 3.3 times power gain with bandwidth broadening of 5.4 Hz over conventional IDEH designs, which translates to 100% PI recovery. The underlying physics of the proposed method is independent of the device scale and is explained using a coupled numerical model.